DISTRIBUTION OF HYDRAULIC CONDUCTIVITY VALUE AND INTERACTION BETWEEN GROUNDWATER â SURFACE WATER MODELLING ON CITARUM UPSTREAM SUB-WATERSHED - Anatra Rahmana Effendi, Fabio
The research area is eastern upstream of Citarum sub-watershed which lies in West Bandung Regency, Bandung City, Sumedang Regency, and Bandung Regency. The objectives of this study are (1) to quantify the interactions between groundwater-surface water both spatially and temporally which accommodated with groundwater-surface water exchange rates (GSWER) and (2) to estimate groundwater discharge contribution to monthly peak river discharge in research area. The methods used in this research are field data collection of distribution of soil hydraulic conductivity values, simulation using SWAT-MODFLOW, and estimation of groundwater discharge contribution to monthly peak river discharge. The calculation of water balance with F.J Mock method is also carried out to verify the simulated river discharge data. The lowest hydraulic conductivity value obtained was 2.57×10-5 cm/s on intercalation of lava, breccia, and tuff and the highest was 7.58×10-3 cm/s on lava with an average of 1.05×10-3 cm/s. Comparison of the SWAT-MODFLOW simulation result with study of interaction between groundwater and surface water of Citarum watershed in Majalaya-Ibun Districts conclude that the resolution of the hydraulic conductivity value affects the modeling results. The highest GSWER value generated in the dry season for the effluent system was 13675 m3/day on segment 1 and for the influent 6557 m3/day on segment 3 with an average of -2720 m3/day, while in the rainy season the highest value for the effluent system was 16126 m3/day on segment 1 and for influent 1226 m3/day on segment 1 with an average of -9264 m3/day. The contribution of groundwater discharge to monthly peak river discharge in the study area ranged from 5.59% for segment 2 to 33.19% for segment 3.